2017
DOI: 10.1093/humrep/dex227
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind randomized controlled trial of letrozole versus clomiphene citrate in subfertile women with polycystic ovarian syndrome

Abstract: STUDY QUESTIONWould letrozole as a primary ovulation induction agent generate better pregnancy rates than clomiphene citrate (CC) in subfertile women with anovulatory polycystic ovarian syndrome (PCOS)?SUMMARY ANSWERParticipants receiving letrozole as a primary treatment achieved a significantly (P = 0.022) higher clinical pregnancy rate per patient (61.2%) compared to CC (43.0%).WHAT IS KNOWN ALREADYAccording to a recent Cochrane systematic review (2014), letrozole appears to improve live-birth (LB) and pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
119
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(126 citation statements)
references
References 26 publications
7
119
0
Order By: Relevance
“…Fifty six publications reporting on 57 trials fulfilled the eligibility criteria, as one study 56 included two individual trials (appendices 2 and 3).Five studies 35 36 47 52 67 were crossover studies and eight studies 35 44 54 61 66 77 86 87 were reported in conference abstracts. Publication dates ranged from 1966 to 2015, with 45 trials published in the last 10 years.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Fifty six publications reporting on 57 trials fulfilled the eligibility criteria, as one study 56 included two individual trials (appendices 2 and 3).Five studies 35 36 47 52 67 were crossover studies and eight studies 35 44 54 61 66 77 86 87 were reported in conference abstracts. Publication dates ranged from 1966 to 2015, with 45 trials published in the last 10 years.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Despite evidence of effectiveness and safety in well designed large randomised controlled trials (RCTs), letrozole is still used off label for ovulation induction, since it has not been approved by the US Food and Drug Administration (FDA) for this indication. 6 A 2005 study 7 , including 150 babies, raised some concerns about the teratogenicity of letrozole, but there were major methodological flaws in this study as the intervention group was not well controlled. Two other large studies, including 911 and 470 infants respectively, compared the use of letrozole to CC and spontaneously conceiving women.…”
Section: Resultsmentioning
confidence: 99%
“…The primary outcome measure for letrozole as an OI in the study shows that the overall clinical response in the form of ovulation and pregnancy was 64.2% and 32.8%, respectively, and these results were lower than those seen in other studies (Alizzi FJ [11] , Amer, et al [22] , Palomba, et al [23] ). The lower ovulation and pregnancy rate seen could be due to the and clomiphene resistant (37.3).…”
Section: Discussionmentioning
confidence: 53%